Aula de Trabalho Pedagógico Coletivo na rede estadual paulista: a voz do professor da Diretoria de Ensino da Região de Jacareí - Corral, Alcione Zaniboni (2016)
This piece has as main objective the investigation of the perceptions of the state of Sao Paulo-Brazil public school teachers on Collective Work Pedagogical Class (Aula de Trabalho Pedagógico Coletivo - ATPC), as teacher training opportunities in order to contribute to the qualification of the teaching practice. This study specifically aims to analyze The School´s Years´ Project Plan and The Pedagogical Board of Jacarei and Region Political Projects, explaining concepts and other references to the ATPC available in them; identifying the perception of the teacher about their participation and performance in the form of ATPCs and checking the meaning gathered by the teachers to their experiences in this training space. The different forms of recruitment of teaching staff of the Education Department of São Paulo state, called categories and their influence on the relations established in the collective work were also investigated. The theoretical basis was established considering the São Paulo State official documents related to ATPCs to characterize the current political and studies by authors like Apple, Contreras, Fusari, Gimeno Sacristán, Imbernon and Santos in order to contextualize the investigated reality and define the conceptual references of the analysis. The research used a qualitative approach, the document analysis technique applied to the Plans Managers and Pedagogical Political Project and an online questionnaire with the school teachers to collect data. The results unveil the ideology underlying the curriculum, the perceptions of teachers on the ATPC indicate that there is contribution to the qualification of the teaching practice, however, the most effective participation focuses on categories that are stable and shows inconsistency in the collective work when some categories do not participate and some meetings are not collective. The data demonstrates that training is not built by all members, with evidence of suppression of rights when teachers Category "S" and "V" are unable to take advantage of this training space, indicating that the hiring process also influences the collective work of teachers